Bibliometric Study on IoT Adoption in Smart Manufacturing: Trends, Challenges, and Opportunities - Loso Judijanto; Husain Ali; M Safii; Rasna Rasna; Elkana Timotius (West Science Social and Humanities Studies, 2025)
This bibliometric study investigates the adoption of the Internet of Things (IoT) in smart manufacturing, examining the trends, challenges, and opportunities that have shaped this evolving field from 2000 to 2022. Utilizing data sourced exclusively from Scopus and analyzed through VOSviewer, the research identifies core themes, tracks their progression over time, and highlights the key contributors and collaborations across countries. The analysis reveals a significant shift from basic IoT applications towards more sophisticated integrations like machine learning, digital twins, and enhanced security protocols. The study also underscores the crucial role of international collaboration in advancing IoT research and addresses the pressing challenges such as interoperability, security concerns, and the workforce skills gap. Furthermore, it suggests future research directions, including the need for standardized IoT frameworks and the exploration of sustainable IoT practices. This study provides a comprehensive overview of the IoT landscape in manufacturing, offering insights into its future trajectory and the potential for transformative industry advancements.